Pengaruh Komitmen Afektif terhadap Organizational Citizenship Behavior (OCB) pada Karyawan di Samarinda - Murni, Rizky Anggia; Astuti, Tri (Fakultas Psikologi Universitas Sanata Dharma, 2024)
Organizational Citizenship Behavior (OCB) is a voluntary behavior that is visible and observable that is based on dominant motives or values and can be based on rewards and punishments that come from external sources. One of the factors that influences Organizational Citizenship Behavior (OCB) is affective commitment. This study aims to examine the Effect of Affective Commitment on Organizational Citizenship Behavior (OCB) on employees in Samarinda. The approach used in this study is a quantitative approach. The data collection technique uses a Likert scale with a questionnaire distributed via Google Form to 100 respondents online. This study uses two scales, namely the Affective Commitment scale and the Organizational Citizenship Behavior (OCB) scale. Data analysis uses simple linear regression using Statistical Product and Service (SPSS) with significance values of .001 (p .005), which indicates a significant influence. The coefficient of determination (R²) of .710 or 71% indicates that affective commitment has an influence on Organizational Citizenship Behavior (OCB) on employees in Samarinda.